Relations among maternal physical activity during pregnancy and child body composition - Mudd, L. M. (Obes Sci Pract, 2019)
OBJECTIVE: Physical activity (PA) during pregnancy is associated with lower neonatal fat mass, but associations with child body composition are mixed. The purpose of this study was to examine associations between trimester‐specific pregnancy PA and child body composition at 4 years. METHODS: Participants of the Minnesota Infant Nutrition, Neurodevelopment, and Obesity Study were asked to recall participation in any moderate or vigorous PA in the first (T1), second (T2) and third (T3) trimesters at about 5 years postpartum. Child fat mass and fat‐free mass were measured via air displacement plethysmography at 2 weeks, 3 months and 4 years of age. Multivariate linear regression was used for analyses. RESULTS: Of 51 possible participants, 37 recalled pregnancy PA. Any vigorous PA in T3 was associated with lower child fat mass at 4 years (adjβ = −1.077, p < 0.05). CONCLUSION: Late pregnancy PA may have lasting benefits for child body composition. Replication of these findings is needed in a larger sample with prospective measures.